A tape calendering method as an effective way for the preparation of proton ceramic fuel cells with enhanced performance. (20th August 2016) - Medvedev, D.; Lyagaeva, J.; Vdovin, G.; Beresnev, S.; Demin, A.; Tsiakaras, P.
Graphical abstract: Highlights: A tape calendering method was used for proton ceramic fuel cell (PCFC) fabrication. PCFC possesses system integrity, electrolyte gas tightness and no gas leakage. PCFC exhibits high power density and open circuit voltage values. BaCe0.5 Zr0.3 Y0.2 O3−δ is an electrolyte under SOFC mode at 600–725 °C (ti ≥ 0.95). Abstract: The possibility of proton ceramic fuel cell (PCFC) fabrication, using a tape calendering method (TCM), is demonstrated for the first time for Ba(Ce, Zr)O3 -based proton-conducting electrolytes in the present work. The cell consists of the 30 μm BaCe0.5 Zr0.3 Y0.2 O3−δ (BCZY) electrolyte, the Y0.8 Ca0.2 BaCo4 O7+δ cathode and the reduced 40%BCZY + 60%NiO and 45%BCZY + 55%NiO support and functional anode layers. Phase structure, thermal and electrical characterization of functional materials are discussed. It is found that the maximal power densities (Pmax ) of the fabricated PCFC (174 and 308 mW cm −2 at 600 and 725 °C, respectively) are acceptable for an intermediate-temperature range of operation and comparable with those reported in literature. It is also found that the BCZY electrolyte exhibits very high open circuit voltage (OCV) values (1.141 and 1.079 V at 600 and 725 °C) and, correspondingly, predominant ionic transport (average ions transport number ∼0.99 and 0.95 at 600 and 725 °C). The tape calendering method can be considered as effective strategy for PCFCs fabrication, ensuring the formation of gas-tight electrolytes and acceptable electrochemical properties.